Perjanjian Pinjam Pakai Aset Pemda Lombok Barat Dengan Stie Amm Kota Mataram: (Studi Putusan No.64/G/2020) - Muhamad Izrul Gunawan; Wiwiek Wahyuningsih (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the process of agreement in land use between STIE AMM Mataram and the Government of West Lombok, as well as the legal certainty provided based on the PTTUN Surabaya decision. This study uses normative legal research using the Legislative and Conceptual approaches. After the researcher carried out the investigation, it was found that the use of West Lombok government land by the STIE AMM was based on a borrow-to-use agreement as outlined in the Regent's Decree No. 254/593/287 concerning the Transfer of Use of Land Controlled by the Government of West Lombok, related to the Decree of the Regent of West Lombok Number: 697/72/BPKAD/2020 concerning the Revocation of the Decree of the Regent Number: 254/593/287 concerning the Transfer of Use of Land Controlled by the Level II Regional Government of West Lombok based on Decision No. 132 /B/2021/PTTUN SBY ​​tried and declared the actions of the West Lombok Government categorized as arbitrary actions and ordered the Appellant/Defendant to revoke the Decree of the Regent of West Lombok.